Building Organizational Performance through Trust-Based Leader Member Exchange: Evidence from Rattan SMEs (Architecture Image Studies, 2026)
This study examines how Amanah-based Leader–Member Exchange (LMX) enhances organizational performance by emphasizing trust as a central relational mechanism in small and medium-sized enterprises (SMEs). Drawing on Social Exchange Theory and relational leadership perspectives, the study addresses an important gap in the LMX literature by positioning trust not merely as an outcome, but as a key pathway through which leadership relationships translate into performance outcomes. The research focuses on labor-intensive rattan SMEs in Solo Raya, Indonesia, where organizational performance depends heavily on close leader–employee interactions and relational coordination. Using a quantitative explanatory design, data were collected through a cross-sectional survey of 189 employees working in rattan SMEs. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the proposed model linking three dimensions of Amanah-based LMX (respect, obligation, and trust) to affective commitment and organizational performance. The results demonstrate strong explanatory power, with the model explaining 78.6% of the variance in organizational performance and 74.5% in affective commitment.The findings reveal that Amanah Trust is the most influential predictor of affective commitment and organizational performance, both directly and indirectly through affective commitment. Respect and obligation dimensions also show positive direct effects on commitment and performance, although their indirect effects through affective commitment are weaker or non-significant. These results indicate that trust serves as the primary relational catalyst that converts ethical and supportive leadership behaviors into sustained performance outcomes in SMEs. This study contributes to the leadership literature by extending Leader–Member Exchange theory through the integration of Amanah-based trust as a central explanatory mechanism, offering a culturally grounded yet broadly applicable framework for understanding leadership effectiveness in resource-constrained organizational contexts. Practically, the findings underscore the importance of trust-oriented leadership development for enhancing commitment-driven performance in SMEs operating in competitive and uncertain environments.